2022
DOI: 10.2147/ijgm.s363959
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors for Male Infertility: A Scoping Review of Published Studies

Abstract: Background: Despite the evidence of declining sperm counts worldwide and the increasing prevalence of male infertility, there has been limited documentation of the potential causes and risk factors for male infertility. With limited methods of primary treatment of male infertility, understanding the causes and risk factors will pinpoint specific lines of prevention. Objective: We reviewed published studies on causes and risk factors for male infertility and identify gaps in the literature enabling more focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 69 publications
(76 reference statements)
0
28
0
Order By: Relevance
“…In addition, an insightful review has summarized that there are potential associations between male infertility and the risk of chronic disease, co-morbidities, cardiovascular disease and cancer development, so male infertility will have more possibilities as a biomarker of future health and mortality ( 4 ). Common causes and risk factors for male infertility have been postulated and/or confirmed in various studies, including smoking, alcohol consumption, drugs, obesity, past or current testicular infections, exposure to environmental toxins, testicular exposure to excessive heat, hormonal disorders, testicular trauma, and ejaculation/erectile dysfunction ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an insightful review has summarized that there are potential associations between male infertility and the risk of chronic disease, co-morbidities, cardiovascular disease and cancer development, so male infertility will have more possibilities as a biomarker of future health and mortality ( 4 ). Common causes and risk factors for male infertility have been postulated and/or confirmed in various studies, including smoking, alcohol consumption, drugs, obesity, past or current testicular infections, exposure to environmental toxins, testicular exposure to excessive heat, hormonal disorders, testicular trauma, and ejaculation/erectile dysfunction ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Male infertility has been attributed to several factors, including problems in spermatozoa caused by insufficient numbers (azoospermia/oligospermia), poor motility and incorrect structure/morphology. Systematic drops in sperm counts have been noted in some articles [5,6] . Based on Okonofua et al study, four broad causes and risk factors of male infertility identified were biological/physiological/genetic causes; behavioral/lifestyle risk factors; environmental factors and socio-demographic risk factors [5] .…”
mentioning
confidence: 95%
“…Systematic drops in sperm counts have been noted in some articles [5,6] . Based on Okonofua et al study, four broad causes and risk factors of male infertility identified were biological/physiological/genetic causes; behavioral/lifestyle risk factors; environmental factors and socio-demographic risk factors [5] . The genetic and biological factors in male infertility that have been identified so far include chromosomal disorders, monogenic diseases, meiosis and endocrine disorders [7] .…”
mentioning
confidence: 95%
“…Inadequate numbers (oligospermia/azoospermia), impaired motility, and defective morphology of spermatozoa have been reported as leading causes of male infertility. [1][2][3][4][5] Semen analysis is mainstay in the evaluation of male infertility. Additionally, advanced diagnostic tests to investigate sperm quality are on a rise and can improve diagnosis and management.…”
mentioning
confidence: 99%
“…2 Male infertility is often poorly responsive to primary treatment and is frequently tackled using secondary measures like intra-uterine insemination, in vitro fertilization, intra-cytoplasmic sperm transfer, and child adoption. [5][6][7] This study was undertaken to help understand the causes and risk factors responsible for male infertility thereby enabling the identification of effective methods for its primary treatment.…”
mentioning
confidence: 99%